Impoliteness strategies used by haters and supporters of presidential candidates in cyber-conflicts - Hasanah, Raidatul; Murni, Sri Minda; Lubis, Fauziah Khairani (Proceedings of English Linguistics and Literature, 2024)
The 2024 Indonesian presidential election is anticipated to be highly contested, with the potential for online hostility to escalate into real-world conflict. This study examines the impoliteness strategies used by supporters and haters of presidential candidates on social media, specifically within Instagram comments. Employing a qualitative approach, the study analyzed a sample of comments, revealing a predominance of negative impoliteness (70%), followed by positive impoliteness (46%). Sarcasm and mock impoliteness were observed in 17% of cases, while bald-on-record impoliteness was the least common (11%). Interestingly, no evidence of withhold politeness was found. These findings highlight the prevalence of online aggression in Indonesian election discourse, underscoring the need for strategies to mitigate the negative impacts of online impoliteness and protect national unity.